The Parable of the Sower: Rooting out White Supremacy and Institutionalized Racism in the church - Sales, Terrelle B.; Rim, Kathy (2023)
This article highlights the parallels between Camara Jones’ Gardener's Tale allegory and Jesus’ Parable of the Sower to invite reflection regarding White Evangelical Christians’ approach to addressing institutionalized racism faced by African Americans and Blacks in the US and the church. Using an interdisciplinary lens that engages sociology, politics, history, theology and biblical exegesis, this article presents a compelling case for the church to cease the practice of compartmentalizing anti-racist movements as “political” and lead the charge through a missional goal to root out institutionalized racism both within the church and American society.
Keywords: biblical justice; Anti-racism; Black American; African American; Jesus Christ; Church; White Evangelical church; Racism; institutionalized racism; White Supremacy